Decoding Lambda API Architectures: Analyzing Monolithic Lambda Functions Versus Fine-Grained Single-Purpose Functions - Balakrishna, Balasubrahmanya (International Journal of Computing and Engineering, 2023)
Purpose: With an emphasis on AWS Lambda specifically, this technical paper explores the trade-offs and architectural considerations between monolithic and single-purpose functions in server less computing systems. Methodology: By examining the effects of using either a monolithic approach or a precisely calibrated, single-purpose function design, we hope to empower developers and architects. We investigate in-depth aspects, including resource usage, application monitoring, scalability, and performance. The approach strongly emphasizes a thorough examination of AWS Lambda's architectural issues, including the methods and resources utilized to produce insightful results. Findings: The results emphasize carefully investigating server less computing's scalability, performance, and resource use, especially regarding single- and monolithic-purpose function architectures. These observations provide concise factors to take into account when developing server less applications. Unique contributor to theory, policy and practice: The last section provides actionable insights to help developers of server less applications make well-informed decisions by condensing knowledge into useful suggestions for maximizing system responsiveness and resource management. The author, coming from an AWS background, is committed to using these technologies to express the concept throughout.